Reliability analysis on the reservoir dam spillway structure using fluid-structure interaction - Zawawi M.H.; Ng F.C.; Azman A.; Tung L.H.; Abustan I.; Mohd Remy Rozainy Z.; Abas A. (IOP Publishing Ltd, 2023)
This paper presents a combined reliability and flow analysis on the spillway of reservoir dam using the numerical fluid-structure interaction (FSI) approach. The spillway is an important structure to the operation of reservoir dam, as it regulates the water flow from upstream to downstream. Therefore, a rapid discharge of water from the reservoir along the spillway will causes possibly flooding at downstream and incurs high structural stress. Using the ANSYS software, the two-way FSI problem of a dam spillway is numerically simulated. Such FSI numerical study able to simultaneously simulate and obtain both the parameters on fluid flow and structural deformation. The current study shows that the downstream has the highest flow velocity; while the highest deformation of 10.7 mm being observed in the connection bridge section. As the general stress level of the overall spillway structure (max. 30.75 MPa) is less than the yield stress of corresponding materials, the spillway will not exhibit any structural failure upon the current discharge mode. Published under licence by IOP Publishing Ltd.